The construction of an interfacial valve-based microfluidic chip for thermotaxis evaluation of human sperm - Li, Zhuoqi (AIP Publishing LLC, 2014)
Thermotaxis has been demonstrated to be an important criterion for sperm evaluation, yet clinical assessment of thermotaxis capacity is currently lacking. In this article, the on-chip thermotaxis evaluation of human sperm is presented for the first time using an interfacial valve-facilitated microfluidic device. The temperature gradient was established and accurately controlled by an external temperature gradient control system. The temperature gradient responsive sperm population was enriched into one of the branch channels with higher temperature setting and the non-responsive ones were evenly distributed into the two branch channels. We employed air-liquid interfacial valves to ensure stable isolation of the two branches, facilitating convenient manipulation of the entrapped sperm. With this device, thermotactic responses were observed in 5.7%-10.6% of the motile sperm moving through four temperature ranges (34.0-35.3 °C, 35.0-36.3 °C, 36.0-37.3 °C, and 37.0-38.3 °C, respectively). In conclusion, we have developed a new method for high throughput clinical evaluation of sperm thermotaxis and this method may allow other researchers to derive better IVF procedure.